Farmers Adoption Level On The Use Of Living Supports On Pepper Plants (Piper nigrum L.) In Pemali District Bangka Regency - Arie Hapsani Hasan Basri (JASc (Journal of Agribusiness Sciences), 2021)
Adoption is the acceptance of an innovation in farming that is influenced by many factors. This research discussed the level of farmer adoption and the factors that influence farmers in the use of living supports on pepper plants. The research was conducted in Pemali District, Bangka Regency from March to May 2021. Data collection methods were observation and interview methods using questionnaires that had been tested for validity and reliability, with data analysis methods using likert scale and multiple regression tests. The result showed the level of farmer adoption level on the use of living supports on pepper plants is high with a percentage 75,25%, for regression analysis it has a regression equation that is Y= - 0,573 0,129X1 + 0,124X2 + 0,623X3 + 0,203X4. Further test using t-count shows that the characteristics of innovation factor has a very significant influence and access to information media factor has a significant influence with the t-count value greater than t-table.